The Application of Resolvin D1-Loaded Gelatin Methacrylate in a Rat Periodontitis Model - Zhe Xing; Jing Liu; Jiazheng Cai; Xiaofeng Jiang; Jingwen Liang; Masahito Fujio; Elin Hadler-Olsen; Jing Wang; Alpdogan Kantarci; Ying Xue (Pharmaceutics)
Objective: To evaluate the drug release, cytocompatibility with periodontal ligament cells (PDLCs), and therapeutic efficacy of GelMA hydrogel loaded with resolvin D1 (RvD1) in treating rat periodontal inflammation and alveolar bone damage. Methods: An RvD1 complexed with GelMA was prepared, and its release kinetics and compatibility with PDLCs were assessed. Rats with induced periodontitis were treated weekly with topical applications of vehicle, GelMA, RvD1, or RvD1 complexed with GelMA for four weeks. Periodontal inflammation and tissue regeneration were evaluated using quantitative PCR (qPCR) and histochemical staining, while alveolar bone repair and regeneration were analyzed through micro-CT. Results: The RvD1 complexed with GelMA effectively released RvD1 and enhanced the proliferation and viability of PDLCs. Compared to RvD1 alone, treatment with RvD1 complexed with GelMA significantly reduced inflammatory cell infiltration, TNF-α and RANKL expression, and osteoclast formation in periodontal tissues. Additionally, it promoted the expression of specific anti-inflammatory and regenerative markers. Micro-CT analysis confirmed significant new bone formation in the RvD1 complexed with GelMA-treated group. Conclusions: RvD1 complexed with GelMA provides sustained drug release and biocompatibility, effectively resolves periodontal inflammation, and promotes tissue regeneration in periodontitis.